Numerical simulation of dynamic processes during operation of emergency brake of tunnel escalators - Kozlov M.N. (Naučno-Tehničeskij Vestnik Brânskogo Gosudarstvennogo Universiteta)
The emergency brake is an essential element of the escalator safety system, designed to prevent the negative consequences of emergency situations. However, due to the very rare operation of this mechanism, the effect of dynamic loads on its elements has not been sufficiently studied. In addition, the use of normally closed brakes with a constant torque requires a more detailed study of the setting of the contacting surfaces. The purpose of this work is to evaluate the operating parameters, as well as the stress-strain state of the emergency brake elements using virtual modeling in the Comsol Mutliphysics software package, under conditions of different loading of the escalator and the area of setting of the friction surfaces. The article presents the results of numerical simulation of the dynamic loading mode of the clutch bolts of the ratchet emergency brake device of the tunnel escalator. The case of the occurrence of an abnormal node position as a result of the formation of a grip on the working surfaces of the friction device is considered. The results of a numerical experiment performed in the program of finite element modeling of Comsol Multiphysics in a three-dimensional nonstationary formulation are presented.